Better safe than sorry: towards appropriate water safety plans for urban self supply systems - Kilanko-Oluwasanya, Grace Olutope (Cranfield University, 2009)
Self Supply Systems (SSS) can be defined as privately owned household level water sources. The research focus is on urban self supply hand dug wells in Abeokuta, Nigeria. Self supply wells serve an estimated 45% of Abeokuta’s population. SSS can be gradually upgraded to improve water quality, but water quality can also be improved through effective risk management. The World Health Organization (WHO) has developed a risk management tool known as Water Safety Plans (WSP), but the tool has not been tried for SSS. This research focuses on the relevance of the generic WHO water safety plans tool to SSS, with the aim to develop an appropriate water safety framework for self supply sources to ensure acceptable household water. Water from self supply wells is used for both ingestion and non-ingestion household activities. The water quality of the sources is poor and not safe for consumption with faecal coliform counts in excess of 100 cfu/100 ml of water. Self supply wells in Abeokuta are plagued by four main water safety threats; style of source operation – primarily through bucket and rope -, construction problems, proximity to sources of contamination, and user’s hygiene practices. Users are in denial of the health consequences of unsafe water. There is a predominantly reactive attitude to water safety management. The main source management approaches include access and hygiene management. To appropriate existing WSP to SSS, source and water safety control measures require user acceptability to be sustainable in terms of adoption and compliance. Incentives are needed for the adoption of SSS water safety plans. A two- phase supporting program is necessary: awareness and enlightenment campaigns and relevant training activities. Water safety development for self supply wells need to be initiated and coordinated by an established institution other than the source owners. This research suggests the Department of Public Health as the institution to facilitate the development of water safety plans for SSS in Abeokuta, Nigeria.
Keywords: Nigeria; groundwater; water quality; sanitary survey; risk management; hand dug wells; Abeokuta